The Impact of Psychological Factors on Periodontitis in the Elderly: A Systematic Review - Preethanath, Reghunathan S.; Ibraheem, Wael I.; Meshni, Abdullah A.; Dawood, Tazeen; Alam, Mohammad Nazish; Anil, Sukumaran (European Journal of Dentistry, 2025)
Psychological factors and periodontitis are prevalent in geriatric populations, with evolving evidence suggesting potential associations. This systematic review comprehensively examines and evaluates the bidirectional relationship between psychological factors and periodontitis in older adults. Following PRISMA guidelines, systematic searches were conducted across PubMed, Google Scholar, Scopus, Embase, and Web of Science databases. The research question was structured using the PECO framework (P = older adults aged ≥ 60 years; E = presence of psychological factors; C = absence of psychological factors; O = periodontitis and its severity). Articles were selected based on predetermined inclusion/exclusion criteria, followed by data extraction. The Newcastle-Ottawa Scale assessed risk of bias and methodological quality, while the Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) framework determined evidence certainty. Of 475 studies identified, 13 met the inclusion criteria for qualitative synthesis (8 on depression, 3 on stress, 1 on cognitive impairment, and 1 on examining multiple factors). For depression–periodontitis associations, results were inconsistent: four studies demonstrated positive associations, three found no significant relationship, and one had unclear findings. All three studies investigating stress–periodontitis relationships showed positive associations, suggesting a more consistent connection. The single study on cognitive impairment found significant independent associations with periodontitis after controlling for confounders. Only one longitudinal study (n = 11,454) revealed increased periodontitis risk at both 6-month and 1-year follow-ups in older adults with depression. Based on Newcastle-Ottawa Scale ratings, seven studies were deemed high quality, three moderate quality, and one low quality. GRADE assessment indicated very low certainty of evidence across all psychological factors, primarily due to methodological heterogeneity. This systematic review indicates significant associations between periodontal disease severity and psychological factors, particularly stress and cognitive impairment, in older adults. These findings suggest the importance of integrating psychological assessment into geriatric oral healthcare. More longitudinal research is needed to establish causality and bidirectional relationships, especially in middle- and low-income countries with a rapidly growing geriatric population. Mental health considerations should be incorporated into prevention and treatment strategies for periodontal disease in older adults.
Keywords: periodontitis; psychological factors; older adults; GRADE analysis; oral health; stress; anxiety; depression; cognitive impairment; cardiovascular outcomes